The Contribution of Social Semiotics to Text Understanding in Various Disciplines: A Systematic Literature Review - Batubara, Muhammad Hasyimsyah; Meisuri, Meisuri; Saragih, Amrin (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2024)
-This article investigates the role of social semiotics in enhancing text comprehension across various academic disciplines, addressing a critical gap in interdisciplinary understanding methods. Although previous studies applied social semiotics to specific modes and disciplines, a comprehensive analysis that includes multiple semiotic elements in academic texts remains limited. The objective of this study is to verify how social semiotics can be used to interpret complex, multimodal academic texts, thereby aiding students in diverse fields. By using a Systematic Literature Review (SLR) methodology, the study analyzes findings from 13 relevant articles sourced from Google Scholar between 2020 and 2024. Key findings highlight that social semiotics facilitates understanding by enabling readers to contextualize and interpret multimodal content such as visual elements, data, and narrative structures unique to each discipline. These insights reveal implications for educators in developing interdisciplinary comprehension strategies and underscore the ability of social semiotics as a framework for understanding academic texts holistically. Consequently, this research contributes to the theory and practice of education by providing concrete guidance for improving cross-disciplinary text comprehension, ultimately supporting more effective and inclusive academic learning.